2001
DOI: 10.1890/1051-0761(2001)011[0764:cohdor]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Cascading of Habitat Degradation: Oyster Reefs Invaded by Refugee Fishes Escaping Stress

Abstract: Mobile consumers have potential to cause a cascading of habitat degradation beyond the region that is directly stressed, by concentrating in refuges where they intensify biological interactions and can deplete prey resources. We tested this hypothesis on structurally complex, species-rich biogenic reefs created by the eastern oyster, Crassostrea virginica, in the Neuse River estuary, North Carolina, USA. We (1) sampled fishes and invertebrates on natural and restored reefs and on sand bottom to compare fish ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(87 citation statements)
references
References 44 publications
(41 reference statements)
4
81
0
Order By: Relevance
“…The literature suggests that oyster reef communities of fish and macroinvertebrates are often highly diverse and include many species that are never or only rarely found in adjacent soft-bottom habitats (see Coen et al 1999). Although an association between fish and oyster habitat has been demonstrated (Coen et al 1999;Lenihan et al 2001;Lehnert and Allen 2002), the relative value of such habitat to fish is uncertain. Given the presumed ecosystem function of oyster reefs and their importance to fish (as areas for feeding, reproduction, and recruitment, as well as refugia; Coen et al 1999;Harding and Mann 2001;Lehnert and Allen 2002), it is not surprising that the overall fish biomass estimates were generally higher at oyster habitat.…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that oyster reef communities of fish and macroinvertebrates are often highly diverse and include many species that are never or only rarely found in adjacent soft-bottom habitats (see Coen et al 1999). Although an association between fish and oyster habitat has been demonstrated (Coen et al 1999;Lenihan et al 2001;Lehnert and Allen 2002), the relative value of such habitat to fish is uncertain. Given the presumed ecosystem function of oyster reefs and their importance to fish (as areas for feeding, reproduction, and recruitment, as well as refugia; Coen et al 1999;Harding and Mann 2001;Lehnert and Allen 2002), it is not surprising that the overall fish biomass estimates were generally higher at oyster habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Direct human activity such as physical manipulations to the benthos from dredging can also result in some resident animals abandoning or temporarily avoiding an area and opportunistic species moving in to use the disturbed area (Jennings and Kaiser, 1998). Lenihan et al (2001) found that eutrophication, density stratification and oyster dredging combined to deplete dissolved oxygen in bottom waters in the Neuse River estuary, North Carolina, USA. In response, some fishes (termed 'refugees' by Lenihan et al, 2001) abandoned the area and moved to nearby oyster reefs in well-oxygenated waters, where they accumulated in high densities, which resulted in a rapid depletion of prey populations.…”
Section: Relocations Of Home Rangementioning
confidence: 99%
“…Lenihan et al (2001) found that eutrophication, density stratification and oyster dredging combined to deplete dissolved oxygen in bottom waters in the Neuse River estuary, North Carolina, USA. In response, some fishes (termed 'refugees' by Lenihan et al, 2001) abandoned the area and moved to nearby oyster reefs in well-oxygenated waters, where they accumulated in high densities, which resulted in a rapid depletion of prey populations. Changes in animal density and assemblage composition, therefore, can also result in changes to the availability of resources and the dynamics of competition, which may evoke a relocation response.…”
Section: Relocations Of Home Rangementioning
confidence: 99%
“…Hypoxia is generally a seasonal phenomenon in temperate estuaries, and is usually restricted to deeper water basins, which remain hypoxic for most of the summer. Hypoxic 'dead zones' often form in deep channels (Officer et al 1984); thus, reducing the amount of usable habitat for mobile organisms and concentrating them in shallower zones where oxygen concentrations are relatively high (Pihl et al 1991, Breitburg 1992, Lenihan et al 2001. The spatial and temporal extent of hypoxic water can be dynamic because winds and tides periodically cause hypoxic bottom water to upwell onto shallow, nearshore habitats (Sanford et al 1990, Breitburg 1992, Luettich et al 2000.…”
Section: Introductionmentioning
confidence: 99%